2016
DOI: 10.1051/matecconf/20166705028
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Investigation of the Fracture Behaviors of 2195-T8 Aluminum-Lithium alloy

Abstract: Abstract. In this paper, the tensile crack initiation and propagation behavior of 2195-T8 Aluminum-Lithium alloy was studied by in situ scanning electron microscope observation at room temperature. It was found that cracks initiated at second phases which propagated along the grain boundaries only as T 1 phases could retard crack growth inside grains. With further increase of strain, within the grain a large number of slip bands were produced, resulting in the deflection of the grains, which leaded to transgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The aluminum-lithium 2195 alloy is of great interest to the aerospace industry. During the last decade, the 3rd generation Al-Li alloys 2195 (Al-4.0Cu-1.2Li-0.4Mg-0.4Ag-0.12Zr) received considerable attention from both scientific communities and the aerospace and military industries [7,8,9]. Industrial studies have shown its low density and good mechanical properties such as high strength, high stiffness and fracture toughness, good weldability, excellent elevated temperature and cryogenic mechanical properties, high corrosion resistance, and amenability to superplastic forming [10].…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum-lithium 2195 alloy is of great interest to the aerospace industry. During the last decade, the 3rd generation Al-Li alloys 2195 (Al-4.0Cu-1.2Li-0.4Mg-0.4Ag-0.12Zr) received considerable attention from both scientific communities and the aerospace and military industries [7,8,9]. Industrial studies have shown its low density and good mechanical properties such as high strength, high stiffness and fracture toughness, good weldability, excellent elevated temperature and cryogenic mechanical properties, high corrosion resistance, and amenability to superplastic forming [10].…”
Section: Introductionmentioning
confidence: 99%